(3QSGdI aj ehVhYGJ GdYdhe heHGFgG hZGjGJgG hJYQjaGJgGs - (3GdJhbGJj GdQhej GdMfaj, dWa Gddg (B" (3dWaj (B" (3Hf MSf, J (B904s
(3ChdgG (B:s
(3GdMeO ddg GdefRg CaYGdg ZjQ GdYdd hGdCZQGV agPG cJGH dG jZGOQ UZjQI hdG cHjQI EdG CMUjgG bO JHjfJ ajg ehVhYGJ LejY Ydhe GdYQHjI hGdTQYjI heHGOFgG hCZQGVgG hZGjJgG hJYQjaGJgG HVH eYGbOgG Ydi hLg eG jSHbfj ajg CMO s
(3BNQgG (B:s
(3hGYde Cfj QHeG JQcJ aj HYV GdYdhe HjGf MpqOg Ch ehVhYg Ch eHGOFg Ch ZGjJg Ch ZQVg Ch HjGf GKfjf efgG Gh KdGKI Ch LejYgG KbI HaWfJc hNhaG ef GdEeGed aYdjc HGdJCed ajg Jes
(3Cdag ddSdWGf HGjRjO Hf eMeO Hf eQGOs
(3JHUQI GdeDda (B:s
(3PcQ MGLj NdjaI Cfg obJd YGe (B900 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\242s
(3cTa GdXfhf(B2\ 1905s
Keywords: (3GdagGQS hGdecJHGJs